O ensino de história na Proposta Curricular do Estado de São Paulo (2008-2010): rupturas e continuidades - Valles, Giselda Maria (2012)
This research´s theme is The Teaching History in the Curriculum Proposal of the State of São Paulo, established in 2008 to verify the teaching´s continuities and ruptures, as well as theoretical and methodological assumptions that underlie the proposal. From the propositions brought by the research fields of School Subjects History and Theory Critique of Curriculum, is intended to insert in their proposal in its original historical context, highlighting the conflicts involving cultural selection of educational contents and its meaning for teaching of History. As a research procedure, we chose content analyze, with the object and analyze the source material produced by the Department of Education in the form of Reports Teacher and Student for the History discipline